APRESIASI SENI DALAM MENINGKATKAN SEMANGAT BELAJAR LITERASI EKONOMI - Yopi Nisa Febianti (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
Good teaching and learning activities are teaching and learning activities that are not monotonous and saturating, because when learning is needed an atmosphere that provides comfort for learning so that students' minds stay focused, they also remain eager to continue learning, especially learning economic literacy. This study aims to determine the role of art appreciation as a negative reinforcement in increasing the enthusiasm of learning economic literacy of students during teaching and learning activities. This study used qualitative research methods. The data sources of this research are primary and secondary data. Primary data is data from observations and interviews, while secondary data is documentation (in the form of photographs). The participants of this research were level 2A students of the Economic Education Study Program FKIP Swadaya Gunung Jati University, who took 26 Kapita Selekta courses in Economic Education. Data analysis was performed qualitatively, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the analysis show that negative reinforcement that is positive, namely punishment with art appreciation can increase the enthusiasm of learning economic literacy of students, can also provide opportunities for students to appear in front of the class in order to hone and develop their talents and interests in poetry as well as singing, even if only on a scale The conclusion of this research is the appreciation of art, boredom and boredom that afflict students can be overcome. It only depends on the lecturer, when the right time for art appreciation is done while studying. Art appreciation is chosen because everyone likes and loves art, especially music. In this way, in addition to the punishment given can entertain and create a pleasant learning atmosphere, it can also hone the talents and interests of student art that are rarely displayed in public, especially in front of classmates and lecturers. Keywords: Art appreciation, enthusiasm for learning, economic literacy.